Solar Power Generation System at Household Scale - Josephin Sundah; Betsi Rooroh; Veny Vita; Ponggawa Putra Wolley; Jeremy Ambar; Rolando Kamura; Feiby Tangon; Christofel Langitan; Natanael Tumangkeng (Interdisciplinary Journal of Advanced Research and Innovation, 2025)
Solar power plants are renewable energy systems that utilize sunlight as a power source to generate electricity. The conversion of light energy into electrical energy is achieved through the photovoltaic effect. The process of converting solar energy into electrical energy is made possible by photovoltaic solar panels, which convert solar light energy into electricity. This technology began to be widely known and began to be widely used. Its use is widespread, ranging from large factories, office buildings, commercial buildings, shopping centers, hospitals, hotels, and households The purpose of this study is to know and analyze household-scale solar power generation systems. The method used in this study is a literature review, data used in the form of articles in electronic databases such as Google Scholar, in the period 2006 to 2023. The results showed that solar power plants (PLTS) are the right choice to overcome the energy crisis in Indonesia. Solar Power Plant Energy (PLTS) is abundant sunlight. Solar Power Plant System (PLTS) at the household level using Solar Home System (SHS) which is increasingly adopted in Indonesia (especially in households). The implication in this study is to provide a deeper understanding of household-scale solar systems, including the associated advantages and challenges. This can help individuals, institutions, and governments make better decisions regarding the use of renewable energy.